فاعلية المدخل القصصي في تنمية بعض المهارات الصَحية لدى أطفال الروضة المعوقين سمعياً "دراسة تجريبية" - القدسي دانية; الدَباغ نازك جلال (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى الكشف عن فاعلية المدخل القصصي في تنمية بعض المهارات الصَحية لدى الأطفال المعوقين سمعياً في مرحلة رياض الأطفال في عمر (5-6) سنوات, ولتحقيّق هذا الهدف تمّ إعداد برنامج للتدخل المبكر يقوم على استخدام المدخل القصصي لتنمية بعض مهارات الصحة والسلامة لدى الأطفال المعوقين سمعياً في مرحلة الروضة, كما تمّ إعداد مقياس مصور وملون لقياس مهاراتهم الصحية بأبعاده الخمسة(مهارة العناية بأعضاء الحواس, ومهارة استخدام أدوات النظافة الشخصية, ومهارة اختيار الغذاء الصحي, ومهارة مراعاة بعض العادات الصحية, ومهارة العناية بالمعينات السمعية). وقد بلغّت عينة البحث(20) طفلاً وطفلة, تمّ تقسيمهم إلى مجموعتين تجريبية وضابطة, ضمت كل مجموعة (10) أطفال, موزعين بين صم وضعاف سمع وبين ذكور وإناث. وتوصل البحث إلى النتائج الآتية: - فاعلية البرنامج المقترح في تنمية بعض مهارات الصحية لدى أطفال الروضة المعوقين سمعياً. - توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أطفال المجموعتين الضابطة والتجريبية في القياس البعدي على مقياس المهارات الصحية المصور لأطفال الروضة المعوقين سمعياً وأبعاده الفرعية, والفروق هي لصالح المجموعة التجريبية. - توجد فروق ذات دلالة إحصائية بين متوسطات رتب درجات أطفال المجموعة التجريبية في القياسين القبلي والبعدي على مقياس المهارات الصحية المصور لأطفال الروضة المعوقين سمعياً وأبعاده الفرعية والفروق هي لصالح القياس البعدي. This research aims to reveal the effectiveness of the fiction entrance in the development of some health skills in children with acoustic disabilities in kindergarten at the age 5-6 years, and to achieve the objective of this research was the preparation of a program of early intervention is based on the use of the fiction entrance in order to develop some of the skills of health and safety at children with acoustic disabilities in kindergarten. A photographed and colored scale was prepared to measure their health of the five dimensions (skill care of the members of the senses, the skill of using toiletries, the skill of healthy food choices, skill into account some of the healthy habits, and skill of audio aids care). The total sample 20 boys and girls was divided into two groups: experimental and control group, each group included 10 children, divided between the deaf and hearing impaired and between males and females. The search found the following results: The effectiveness of the program proposed in the development of some health skills of kindergarten children with hearing disabilities. There are significant differences between the averages of two children arranged degrees of control and experimental measurement on a scale dimensional life skills, health photographer for kindergarten children with disabilities and hearing sub-dimensions and the differences for the children of the experimental group. There are significant differences between the averages of scores arranged children in the experimental group of tribal and dimensional measurements on a scale of life skills health photographer for kindergarten children with disabilities and hearing sub-dimensions and variances for dimensional measurement.